2019
DOI: 10.1002/kjm2.12090
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with polyp detection during colonoscopy: A retrospective observational study

Abstract: The polyp detection rate (PDR) is an important quality indicator for colonoscopy. Several factors have been shown to be associated with PDR. However, whether the moderate sedation is a factor for polyp detection remains controversial. This study aims to assess factors associated with polyp detection including the moderate sedation factor during colonoscopy. Patients who underwent colonoscopy from June 1, 2014 to May 31, 2015 were enrolled into this retrospective study. Patients with poor colon preparation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…However, the patient population was predominately male (> 95%), and whether their finding applies to female patients is uncertain. Although colorectal polyps is a male predominate disease [ 15 ], the female proportion in our study is approximately 30%, which is much higher than that in the previous study. Therefore, our study has a more balanced patient distribution leading to practical results based on clinical experience.…”
Section: Discussioncontrasting
confidence: 65%
“…However, the patient population was predominately male (> 95%), and whether their finding applies to female patients is uncertain. Although colorectal polyps is a male predominate disease [ 15 ], the female proportion in our study is approximately 30%, which is much higher than that in the previous study. Therefore, our study has a more balanced patient distribution leading to practical results based on clinical experience.…”
Section: Discussioncontrasting
confidence: 65%
“…Fourth, other factors such as withdrawal time and sedation administered were inconsistent or not reported. [ 19 , 20 ] Fifth, our results shown that no statistically significant difference of the advanced lesions detection rate was found. Due to the small sample size of each trial and small number of advanced lesions, type II error appears to be quite likely exist.…”
Section: Discussionmentioning
confidence: 53%
“…20 However, deep-sedated colonoscopy is conducted entirely in the left lateral position because it is difficult to move a deep-sedated patient to change their position, and the supine position during deep sedation may increase respiratory movements, choking rates, and other respiratory problems. 21 Several studies demonstrated that the use of sedation during colonoscopy increased the ADR comparing with unsedated colonoscopy, but they did not mention whether dynamic position changes were performed in unsedated colonoscopy, [22][23][24][25][26] which may underestimate the quality of unsedated colonoscopy. As shown in the present study, the ADRs in all three groups were high and did not differ significantly from each other.…”
Section: Discussionmentioning
confidence: 99%